Involvement of TGF-β signaling pathway-associated genes in the corneal endothelium of patients with Fuchs endothelial corneal dystrophy - Nakagawa, Tatsuya; Honda, Tetsuro; Inagaki, Soichiro; Yuasa, Taichi; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Aouimeur, Ines; Vaitinadapoule, Hanielle; Travers, Gauthier; He, Zhiguo; Gain, Philippe; et al. (Experimental Eye Research, 2025)
This study investigated the involvement of TGF-β signaling pathway-associated genes in the pathogenesis of Fuchs endothelial corneal dystrophy (FECD). The RNA-sequencing analysis of corneal endothelial cells (CECs) from FECD patients revealed significant alterations in multiple TGF-β superfamily genes, with 9 genes upregulated (including BMP6, GDF5, and TGF-β2) and 10 genes downregulated (including BMP2, NOG, and INHBA) compared to controls. Quantitative PCR validation confirmed the elevated expression of GDF5 (3.35-fold in non-expanded and 7.66-fold in expanded TCF4), TGF-β2 (6.17-fold and 11.5-fold), and TGF-β1 (1.78-fold and 1.58-fold) in FECD patients with and without TCF4 trinucleotide repeat expansion. Ex-vivo experiments using donor corneas demonstrated that TGF-β2 stimulation significantly increased the expression of extracellular matrix (ECM) components associated with guttae formation, including fibronectin, types I and VI collagens, and other matrix proteins. Immunofluorescence confirmed increased fibronectin protein expression in the corneal endothelium following TGF-β1 or TGF-β2 treatment. This study provides the first comprehensive analysis of TGF-β superfamily involvement in FECD and suggests that GDF5, found to be upregulated in FECD, may contribute to the disease process. These findings further indicate that dysregulation of TGF-β signaling pathways drives the characteristic ECM accumulation in FECD, potentially offering new therapeutic targets for this progressive corneal disease involving fibrosis-related alterations. Future research is warranted to clarify GDF5's specific role and mechanistic impact on FECD pathogenesis.
CRIS-Team Scopus Importer:2025-04-01
Keywords: FECD; Fuchs endothelial corneal dystrophy; GDF5; RNA-Seq; TGF-β